A state space‐based explicit integration method for real‐time hybrid simulation. Issue 4 (15th September 2015) - Liu, Yanhui; Goorts, Kevin; Ashasi‐Sorkhabi, Ali; Mercan, Oya; Narasimhan, Sriram
Summary: Real‐time hybrid simulation (RTHS) combines experimental testing with numerical simulation. It provides an alternative method to evaluate the performance of structures subjected to dynamic loading such as earthquake or wind. During RTHS, a numerical integration algorithm is employed to directly solve the equation of motion and generate command displacements for the experimental test structure online. This paper presents an improved explicit numerical integration method for RTHS based on discrete state space formulation. The improved integration method utilizes an extrapolation‐based prediction procedure for command displacement by applying a zero‐order hold. The predicted command displacement is then used to compute the final command displacement by applying a first‐order hold. Both the stability and the accuracy of the proposed integration method are investigated using control theory and numerical and experimental simulations. The proposed method demonstrates improved performance compared with other integration methods. The robustness and feasibility of the proposed method were verified through experimental RTHS on two different computational platforms including a National Instruments system and a dSPACE embedded controller. The proposed method may also be implemented on other platforms containing an xPC target and MATLAB environment. By placing the algorithm on the dSPACE system, any dynamically rated actuator with a controller that can receive analog signal may be used for RTHS. Copyright © 2015 John Wiley & Sons, Ltd.